Spectral Domain Optical Coherence Tomography Imaging of Drusen in Non-Exudative Age-Related Macular Degeneration - Gregori, Giovanni (2011)
PURPOSE: To measure drusen area and volume in eyes with non-exudative age-related macular degeneration (AMD) using spectral domain optical coherence tomography imaging (SDOCT). DESIGN: Evaluation of diagnostic technology PARTICIPANTS: One hundred three eyes from 74 patients with drusen METHODS: Patients with drusen secondary to non-exudative AMD were enrolled in this study. Five separate SDOCT scans, each consisting of 40000 uniformly spaced A-scans organized as 200 A-scans in each B-scan and 200 horizontal B-scans, were performed on each eye. Each scan covered a retinal area of 6×6 mm centered on the fovea. A novel algorithm was used to quantitatively assess drusen area and volume. Measurements from the entire scans, as well as in regions contained within 3 mm and 5 mm circles centered on the fovea, were analyzed. Test-retest standard deviations of drusen area and volume measurements were calculated for each eye. MAIN OUTCOME MEASURE: Drusen area and volume RESULTS: The algorithm created drusen maps that permitted both qualitative and quantitative assessment of drusen area and volume. Both the qualitative appearance and the quantitative measurements of drusen area and volume were highly reproducible over the 5 different datasets. The intraclass correlation coefficient (ICC) was above 0.99 for both area and volume measurements on the entire dataset as well as the 3 mm and 5 mm circles. The correlation between lesion size and the test-retest standard deviations can be eliminated by performing a square-root transformation of the area measurements and a cube-root transformation of the volume measurements. These transformed data allowed for the inclusion of all drusen sizes in the calculation of an estimated single pooled test-retest standard deviation which will be useful for longitudinal studies of drusen natural history. CONCLUSIONS: A novel algorithm for the qualitative and quantitative assessment of drusen imaged using SDOCT was shown to be highly reproducible. The ability to assess drusen volume reliably represents a new quantitative parameter to measure in AMD and may be useful when assessing disease progression, particularly in trials for treatments of non-exudative AMD.